Glycan Therapeutics: Resurrecting an Almost Pharma‐Forgotten Drug Class. Issue 8 (24th August 2018) - Paderi, John; Prestwich, Glenn D.; Panitch, Alyssa; Boone, Tom; Stuart, Kate
Abstract: Despite their enormous potential, glycans as therapeutics yet remain a widely untapped drug class. This overview shares the viewpoint that glycans have been aptly termed the "dark matter" of biology and have thus been largely ignored for decades. Provided herein is a background on the multiple structures and functions of glycan therapeutics, and focuses on examples and case studies of the glycan therapeutics in clinical use or in a clinical development. Perspectives on various hurdles are also provided, such as regulatory or scientific messaging and how these can influence the clinical development of this drug category. Finally some of the necessary changes in perception, education, and research infrastructure for continued support and advancement of this promising category of therapeutics are described. Abstract : Glycans as therapeutics remain a largely untapped drug class, this reflects a historical lag, not lack of therapeutic potential or biological relevance. This overview highlights glycan therapeutics that are in clinical development or approved for clinical use and perspectives on how infrastructural changes can improve the perception and clinical development of this drug class.